2020
DOI: 10.1017/s1047951119003317
|View full text |Cite
|
Sign up to set email alerts
|

Changes in valvular regurgitation in mid-term follow-up of children with first attack acute rheumatic fever: first evaluation after the updated Jones criteria

Abstract: Aim:In present study, we aimed to evaluate the changes in valvular regurgitations in mid-term follow-up of children with first attack acute rheumatic fever diagnosed after updated Jones criteria.Materials and methods:The medical records of the children diagnosed with acute rheumatic fever between June 2015 and November 2018 were evaluated retrospectively. When compared to the findings during diagnosis, the changes in the degree of valvular regurgitation in the last visit were coded as same, regressed, or disap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…There was also no significant difference among these groups by carditis. The increase in ASO titer, which indicates that the streptococcal infection has passed, is also a supportive finding [1,2]. Accordingly, one major and two minor or two major criteria must be present in the first attack, which is one of the Jones criteria.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…There was also no significant difference among these groups by carditis. The increase in ASO titer, which indicates that the streptococcal infection has passed, is also a supportive finding [1,2]. Accordingly, one major and two minor or two major criteria must be present in the first attack, which is one of the Jones criteria.…”
Section: Discussionmentioning
confidence: 83%
“…ARF is diagnosed based on the Jones Criteria, revised by the American Heart Association in 2015. These criteria recommend different diagnostic approaches for low and medium/high-risk populations [1], with Turkey falling into the medium/high-risk group [2]. Familial Mediterranean fever (FMF) is a hereditary autoinflammatory disorder characterized by serosal inflammation (peritonitis, pleuritis, and arthritis) and recurrent fever attacks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluations of the revised Jones criteria have reported that the changes improve the diagnosis of ARF among moderate and high‐risk populations 23 and allow to properly assess the risks associated with the occurrence of latent RHD 24 . A Turkish study involving 50 children reported that the updated Jones criteria prevented under diagnosis of ARF in 18% of the children 25,26 . In addition, other studies have reported that the changes will lead to better clinical outcomes for the disease, through earlier disease identification 27,28 …”
Section: Resultsmentioning
confidence: 99%
“…24 A Turkish study involving 50 children reported that the updated Jones criteria prevented under diagnosis of ARF in 18% of the children. 25,26 In addition, other studies have reported that the changes will lead to better clinical outcomes for the disease, through earlier disease identification. 27,28…”
Section: Diagnosis Of Acute Rheumatic Fevermentioning
confidence: 99%